Magyarország vasúti infrastruktúrájának alakulása Trianon és a Bécsi döntések tekintetében - Miszlay, Zsolt (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
The 4th of June 1920. dictated peace of Trianon’s forced onto Hungary the borders and developed structures were 1938 between 1941 they changed again as a result of feedbacks. The railway system forming Hungary’s traffic spine played a deciding role in the form-ing of the borderlines, his planning. The regional directions between 1920-1947, border modifications at the same time not Hungary meant his changes to his railway system only. The railway infrastructure changed it in a big measure and not in a last row the service staffs situation. Present lecture shows it the border changes background caused by, the railway infra-structure presents his establishment, with a strange look onto the employees’ situation.